Attitudes Toward Same-Sex Parents: Examining the Antecedents of Parenting Ability Evaluation. Issue 3 (22nd October 2020) - Di Battista, Silvia; Paolini, Daniele; Pivetti, Monica
Abstract: Hostility toward same-sex parenting is widespread. Literature supports one persistent argument against same-sex parenting which focusses on the concern for children's wellbeing, whereas lesbian and gay parents' ability is sometimes evaluated positively. In particular, the belief that children need both a father and a mother impacts the evaluation that same-sex parents are unfit to raise well-adjusted children. The present research aimed to investigate linking mechanisms and conditional processes underlying the evaluation of same-sex parents' ability. Cisgender heterosexual Italian participants ( N = 320) read one of four vignettes describing a family situation – two types of same-sex (step)parents (i.e., lesbian and gay (step)parents) vs. two types of different-sex (step)parents (i.e., heterosexual (step)parents) – in which a child misbehaved in the context of a mild family disagreement. After reading the vignette, the participants rated parenting ability and to what extent the child's misbehavior was attributable to the parenting relationship. Moderated-mediation analyses indicated that same-sex (step)parents were perceived as being less capable parents compared to different-sex (step)parents by giving them greater responsibility for the child's misbehavior, among participants with medium and high levels of gender role beliefs. Implications for research on sexual discrimination are discussed.